One-dimensional weak antilocalization effect in 1T′-MoTe2 nanowires grown by chemical vapor deposition. (23rd April 2021) - Chen, Jiancui; Zhou, Zhang; Liu, Hongtao; Bian, Ce; Zou, Yuting; Wang, Zhenyu; Zhao, Zhen; Wu, Kang; Yang, Haitao; Shen, Chengmin; Cheng, Zhi Gang; Bao, Lihong; et al.
Abstract: We present a chemical vapor deposition method for the synthesizing of single-crystal 1T′-MoTe2 nanowires and the observation of one-dimensional weak antilocalization effect in 1T′-MoTe2 nanowires for the first time. The diameters of the 1T′-MoTe2 nanowires can be controlled by changing the flux of H2 /Ar carrier gas. Spherical-aberration-corrected transmission electron microscopy, selected area electron diffraction and energy dispersive x-ray spectroscopy (EDS) reveal the 1T′ phase and the atomic ratio of Te/Mo closing to 2:1. The resistivity of 1T′-MoTe2 nanowires shows metallic behavior and agrees well with the Fermi liquid theory (<20 K). The coherence length extracted from 1D Hikami–Larkin–Nagaoka model with the presence of strong spin–orbit coupling is proportional to T −0.36, indicating a Nyquist electron–electron interaction dephasing mechanism at one dimension. These results provide a feasible way to prepare one-dimensional topological materials and is promising for fundamental study of the transport properties.